2018
DOI: 10.1016/j.tranon.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Serum Chemokines and Clinical Outcome in Patients with Advanced Biliary Tract Cancer

Abstract: BACKGROUND: Biliary tract cancers (BTCs) are known to have a dismal prognosis. A number of chemokines play important roles in the progress of BTCs. However, the serum levels of chemokines in BTCs have not yet been explored. METHODS: The sera of healthy donors (n = 8) and patients with BTCs who were enrolled in second line sunitinib trials (n = 27) were collected. The concentrations of three kinds of chemokines (CXCL5, CXCL8 and CXCL12) were measured using ELISA assay. The median concentrations of chemokines we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The follow-up time ranged from 23 months to 180 months. Ten different types of cancer were involved in the enrolled studies including intrahepatic cholangiocarcinoma (n = 2) [ 27 , 31 ], lung cancer (n = 3) [ 26 , 32 , 33 ], colorectal cancer (n = 3) [ 34 36 ], biliary tract cancer (n = 1) [ 10 ], breast cancer (n = 1) [ 5 ], bladder cancer (n = 1) [ 19 ], glioma (n = 1) [ 18 ], pancreatic cancer (n = 1) [ 25 ], hepatocellular carcinoma (n = 1) [ 24 ] and nasopharyngeal carcinoma (n = 1) [ 37 ]. Among these studies, OS (n = 14), DFS (n = 3), PFS (n = 3) and RFS (n = 3) were estimated as survival outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up time ranged from 23 months to 180 months. Ten different types of cancer were involved in the enrolled studies including intrahepatic cholangiocarcinoma (n = 2) [ 27 , 31 ], lung cancer (n = 3) [ 26 , 32 , 33 ], colorectal cancer (n = 3) [ 34 36 ], biliary tract cancer (n = 1) [ 10 ], breast cancer (n = 1) [ 5 ], bladder cancer (n = 1) [ 19 ], glioma (n = 1) [ 18 ], pancreatic cancer (n = 1) [ 25 ], hepatocellular carcinoma (n = 1) [ 24 ] and nasopharyngeal carcinoma (n = 1) [ 37 ]. Among these studies, OS (n = 14), DFS (n = 3), PFS (n = 3) and RFS (n = 3) were estimated as survival outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Chemokines and their receptors could bring about the transcription of target genes involved in cell invasion, motility, survival and interactions with the extracellular matrix, which can induce migration, chemotaxis and rearrangement of the cytoskeleton in the target cell, and therefore promote multiple physiological functions of cells, including cell growth, development, differentiation and apoptosis [ 6 9 ]. Over the past few years, accumulating evidence has revealed that chemokines play pivotal roles in progression of tumor [ 10 ]. Chemokines produced by tumor and stromal cells can induce the expression and distribution of tumor-associated leukocytes, trigger angiogenesis, contribute to the growth and metastasis of malignant cells and generate fiber keratinocytes [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous studies, more than 14 different malignant tumor types, including breast cancer [15], bladder cancer [16], non-small cell lung cancer [17], gastric cancer [18], head and neck squamous cell carcinoma [19], cholangiocarcinoma [20], hepatocellular carcinoma [21], prostate cancer [22], pancreatic cancer [23], colorectal cancer [24], glioma [25], endometrial cancer [26], nasopharyngeal carcinoma [27], and squamous carcinoma of larynx [6], had high expression of CXCL5 when compared to para-carcinoma or normal tissues (Table 1). By identifying and validating the genes regarding the development of gastric cancer, researchers have found that CXCL5, as one of the substances, was associated with early stages of the disease [28].…”
Section: Overexpression Of Cxcl5 In Tumorsmentioning
confidence: 99%
“…A recent meta-analysis aimed to evaluate the prognostic significance of CXCL5 in CCA patients, revealed that CXCL5 overexpression was inversely correlated with overall survival [ 90 ]. Another recent study, analyzing serum chemokine profiles in CCA, reported that CXCL5 was higher in CCA patients, compared to healthy subjects, and CXCL5 levels correlated with poor prognosis [ 91 ]. These reports clearly point at this chemokine as an important player in tumor progression and a possible novel prognostic marker for CCA.…”
Section: Cxcl5-cxcr2mentioning
confidence: 99%